2001
DOI: 10.1542/peds.108.2.283
|View full text |Cite
|
Sign up to set email alerts
|

Switching to Gatekeeping: Changes in Expenditures and Utilization for Children

Abstract: Parents of children with a chronic condition were much less likely than other parents to switch to a gatekeeping plan. Switching to gatekeeping was associated with reduced visits to specialists but did not increase the involvement of primary care physicians in the management of children with chronic conditions. The implications of these findings for the health of children are unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
4

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 21 publications
2
37
0
4
Order By: Relevance
“…41 Managed care efforts have generally not improved the provision of appropriate services for these children. 42 The Supplemental Security Income (SSI) program, while providing important cash and Medicaid benefits for some of the most seriously affected children, does not make provisions for establishing systems of care. In addition, proposals to extend coverage for "basic care" to currently uninsured children by eliminating specialized benefits for chronically ill children can only exacerbate these financial disincentives.…”
Section: Implications For Practice and Policymentioning
confidence: 99%
“…41 Managed care efforts have generally not improved the provision of appropriate services for these children. 42 The Supplemental Security Income (SSI) program, while providing important cash and Medicaid benefits for some of the most seriously affected children, does not make provisions for establishing systems of care. In addition, proposals to extend coverage for "basic care" to currently uninsured children by eliminating specialized benefits for chronically ill children can only exacerbate these financial disincentives.…”
Section: Implications For Practice and Policymentioning
confidence: 99%
“…Researchers have demonstrated decreases in costs associated with PCCM programs (Martin et al 1989;Rask et al 1999;Ferris et al 2001a), while others have found little effect, or even cost increases (Schoenman, Evans, and Schur 1997;LoSasso et al 2000;Escarce et al 2001;Ferris et al 2001b). However, many of these studies have been limited by a small sample size, limited program duration, inability to measure the cost shifting away from inpatient and towards outpatient care that one would expect, and a lack of adequate theoretical and statistical methods.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may be due to the restrictions placed on use in HMO systems (eg, referrals are needed) but also may reflect a selection bias of sicker children into non-HMO care. 19,20,29 When the results for privately insured children were stratified by chronic condition/disability status, only children without chronic conditions or disabilities had lower use of specialists compared with non-HMO children. These data cannot help us understand whether this reflects HMOs reducing discretionary use among the privately insured, whether HMOs are reducing needed care among the privately insured, or whether other factors (eg, selection bias) account for this finding.…”
Section: Discussionmentioning
confidence: 99%